Usability Evaluation of a Desktop Library Application Using the System Usability Scale - Gunardi, Kahfi; Hardiyanti, layli; Wijaya, Abdun; Arnilia, Okma; Sujana, Fadhlan Ridhwana (Journal of Applied Informatics Science, 2025)
This study aims to evaluate the usability of an offline desktop library application developed using Java Swing and integrated with an iReport feature. The evaluation employed the System Usability Scale (SUS) using a descriptive quantitative approach. Data were collected from 28 respondents consisting of librarians and library administrators as the primary system users. The results show that the application achieved an average SUS score of 62.77, which falls into the marginal acceptability range, corresponding to Grade D and an “OK” adjective rating, and below the standard SUS benchmark score of 68. These findings indicate that the application adequately supports basic library operations but still exhibits usability limitations, particularly in interface consistency, user confusion, and reliance on technical assistance. Consequently, improvements in interface design and user experience are necessary to enhance the overall usability of the application.